Microsoft Dynamics AX 2012 R3 reporting cookbook : over 90 recipes to help you resolve your new SSRS reporting woes in Dynamics AX 2012 R3 /: over 90 recipes to help you resolve your new SSRS reporting woes in Dynamics AX 2012 R3. (2015) - Agarwal, Deepak; Elangovan, Kamalakanna; Aggarwal, Chhavi
No abstract available